PENGEMBANGAN E-MODUL DENGAN APLIKASI 3D PAGEFLIP PROFESSIONAL UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN IPA KELAS 5 SEKOLAH DASAR - Istichomah Istichomah; Sri Utaminingsih; Erik Aditia Ismaya (Journal Prakarsa Paedagogia, 2021)
This study aims to: Determine the improvement of E-Module with the 3D PageFlip Professional application to improve learning outcomes in science learning in grade 5 elementary schools. This type of research is a Research and Development with a non-randomized subject experimental method pre-test post-test control group design. With respondents, the number of students of SDN Gugus Sunan Muria, Demak District was 280 students. This study uses a quantitative approach. The results of this study indicate the highest value obtained in the control group is 84 and the lowest value is 55 with an average of 67.The highest score obtained in the experimental group is 93 and the lowest score is 67 with an average value of 80 indicating that the average value of the experimental group is greater than the control group experienced a significant difference. The data from the t test shows that t count> t table, namely 26.041> 1.6503 and the N-Gain value is in the high category and the interpretation is very effective. Based on this research it is requested that to improve student learning outcomes using e-modules by using the 3D Pageflip professional application.